Phlebotomines in forest parks and other forest fragments of the São Paulo city, State of São Paulo, Brazil - Fernandes Bertoletti Gonçalves, Elisabeth (2018)
Reports of cutaneous leishmaniasis cases in areas in and near urban parks in the city of São Paulo     since the 1970s, and the spread of visceral leishmaniasis since the end of the 1990s led the Centro     de Controle de Zoonoses (currently the Divisão de Vigilância de Zoonoses) of the municipality     of São Paulo to undertake systematic collections of phlebotomine sand flies in 12 forested areas,     represented by 10 parks: Alfredo Volpi, Anhanguera, Cantareira (Núcleo Pedra Grande), do Carmo,     Ecológico Tietê, Fundação Parque Zoológico, Guarapiranga, Jaraguá, Previdência and Tenente     Siqueira Campos (Trianon), and two fragments of residual forest: of the Instituto Butantan and     of the Secretariat of Agriculture of the state of São Paulo. The collections were carried out using     automatic light traps, New Jersey (NJ) and Center of Disease Control (CDC) types, between     1981 and 2001. In the Guarapiranga and Tenente Siqueira Campos (Trianon) parks the collections     were negative. In the all other areas 2,638 sand flies (79% female and 21% male) of 23 species,     belonging to 11 genera, were captured: Brumptomyia (5), Evandromyia (1), Expapillata (1),     Lutzomyia (1), Martinsmyia (1), Migonemyia (1), Nyssomyia (3), Pintomyia (3), Psathyromyia     (3), Psychodopygus (3) and Sciopemyia (1), and also four taxa identified only at the genus level.     The Cantareira park presented the greatest species richness (15 species + 1 Brumptomyia sp.).     Pintomyia fischeri was collected at all the above sites and with the exception of the residual     forest of the Instituto Butantan, where Mg. migonei was the most frequent, it predominated at all     the other sites. These two species as well as Nyssomyia intermedia, Ny. neivai and Ny. whitmani,     collected at some of the sites, are considered to be vectors of Leishmania braziliensis, one of     the agents of cutaneous leishmaniasis. Lutzomyia longipalpis, the main vector of the visceral     leishmaniasis agent, was not found in this study .